Tingkat Kecemasan Remaja Wanita Terhadap Siklus Menstruasi Selama Pandemi Covid-19 Di SMAN 1 Maluku Tenggara - Tety Ripursari; Feni Widiasari (Universitas Islam Madura, 2023)
Increased anxiety in adolescent girls causes the production of estrogen, progesterone and various other hormones in the body to become unstable. causing irregular menstrual cycles. Caused the effect of stress by the changes in life during the Covid-19 pandemic. The purpose of this study was to determine the effect of female adolescent anxiety levels on the menstrual cycle during the Covid-19 pandemic at Public High School 1 Maluku Tenggara. The design of this research is observational analytic with a cross sectional approach. Respondents were taken by simple random sampling technique. The population is 175 with a sample of 64 people. The results of statistical tests using logistic regression. The results of data analysis show that the significance level is 0.001 < = 0.05 so that H0 is rejected and H1 is accepted, thus there is an Influence of Adolescent Girls' Anxiety Levels on Menstrual Cycle During the Covid-19 Pandemic Period at Public High School 1 Maluku Tenggara. It is recommended for young women who experience anxiety to convey their complaints and problems to counseling teachers at schools and health workers so that they can help overcome their problems and reduce their anxiety.